Transformasi Pembelajaran Teacher-Centered ke Student-Centered melalui Pembelajaran Berdiferensiasi dalam Microteaching - Nurmayani Nurmayani; Yuni Hajar; Keysha Nadapdap; Sara Manurung; Nenny Sipangkar; Lena Sagala; Rahma Yanti; Marcella Panjaitan (Jurnal Keluarga Sehat Sejahtera, 2026)
This study aims to describe the strategy of implementing differentiated learning to create active students and avoid teacher-centered learning patterns in the microteaching activities of Grade 5 students at SD Swasta Kasih Bapa Percut. The background of this research is the dominance of teacher-centered patterns in the learning process, which results in low active participation of students and suboptimal development of individual learners’ potential. This study uses a descriptive qualitative approach with observation, interview, and documentation methods. The research subjects were student teachers conducting microteaching and Grade 5 students at SD Swasta Kasih Bapa Percut. The results indicate that the implementation of differentiated learning through three main aspects content differentiation, process differentiation, and product differentiation significantly shifts the learning pattern from teacher-centered to student-centered. Applied strategies include: the use of various learning resources according to students’ learning styles, providing task choices based on learning readiness, interest, and learning profiles, as well as diverse authentic assessments. The resulting impacts include increased student activeness, learning motivation, and critical thinking skills. This study recommends that differentiated learning be established as the primary approach in microteaching practice as a provision for prospective teachers who are responsive to the diversity of learners.